Implementation Mechanism of Internal Operational System of Islamic Banking - Risna Wati; Anggun Okta Fitri (Al-Muamalah: Jurnal Ekonomi Islam, Filantropi dan Perbankan Syariah, 2025)
The Islamic banking system is a system that prioritizes the principle of profit sharing, where profits are obtained fairly and mutually between banks and customers. Based on Islamic law, this system emphasizes fairness, honesty, and Ethics in every transaction, as well as avoiding speculative practices and usury. This study aims to analyze the implementation mechanism of the internal operational system of Islamic banking, assess its compliance with Sharia principles, and measure its effectiveness and efficiency in operations. The method used in this study is qualitative, focusing on an in-depth understanding of the practices and challenges faced by Islamic banking. Through a review of the literature, including books, articles, and related documents, this study explores how sharia principles are applied in bank operations, as well as factors that support their successful implementation. The results showed that Islamic banking in Indonesia has experienced rapid development and become an indicator of the success of the Islamic economy. Islamic banks not only function as an intermediary institution, but also as an agent of social change oriented to the welfare of society. By prioritizing the principles of partnership, transparency, and accountability, Islamic banks strive to provide services that are in accordance with Islamic values. However, challenges remain in the implementation of its operating system, including public awareness of Sharia products and supporting regulations. This study recommends the need for increased understanding and education about Islamic banking among the public, as well as strengthening regulations to support Islamic bank operations. Thus, it is expected that Islamic banks can contribute more to the economic welfare of the community as a whole.